2017
DOI: 10.31234/osf.io/5fe98
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do puzzle pieces and autism puzzle piece logos evoke negative associations?

Abstract: This study examined whether puzzle-piece images evoke negative associations in the general public.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Autism as a puzzle. 119,120 Autism as part of neurodiversity Autism as an epidemic. 121 Autism as increasingly recognized/diagnosed AVOIDING ABLEIST LANGUAGE conceptualizations about the nature of autism.…”
Section: The Impact and History Of Language Used To Talk About Autismmentioning
confidence: 99%
“…Autism as a puzzle. 119,120 Autism as part of neurodiversity Autism as an epidemic. 121 Autism as increasingly recognized/diagnosed AVOIDING ABLEIST LANGUAGE conceptualizations about the nature of autism.…”
Section: The Impact and History Of Language Used To Talk About Autismmentioning
confidence: 99%
“…Examples of social accessibility would be content that explicitly spells out language pragmatics, or content that takes social or cultural context into account; for example, avoiding the use of the jigsaw-puzzle symbol for autism because in Autistic and neurodiversity culture, this symbol is considered dehumanizing. 35,36 As guiding principles for physical accessibility, we used the principles of the WCAG, the most widely-used Web accessibility standard: sites must be perceivable (can users make it out? ), operable (can it be controlled?…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…For example, some CrimRxiv Divergent perspectives: Autistic adults' perceptions of the police 19 respondents reported that these campaigns made them feel safe, while others reported that these efforts put autistic individuals at increased risk of a negative police encounter because these initiatives were perceived to indicate a level of police awareness that was not truly reflected in reality. The division over the imagery associated with autism and autistic causes in particular has long been a point of debate within the autistic community, with many seeing the use of the puzzle piece as particularly harmful and problematic (see Gernsbacher et al, 2018). Respondents were similarly divided in this survey, with some having very positive perceptions of these symbols and messages and others having negative reactions to the use of the 7.…”
Section: Discussionmentioning
confidence: 99%